2012
DOI: 10.1111/j.1468-0289.2012.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese living standards, 1720–1980, in European comparison: heights, income, and human capital1

Abstract: When and why did the Portuguese become the shortest Europeans? In order to find the answer to this question, we trace the trend in Portuguese living standards from the 1720s until recent times.We find that during the early nineteenth century average height in Portugal did not differ significantly from average height in most other European countries, but that when, around 1850, European anthropometric values began to climb sharply, Portugal's did not. In a panel analysis of 12 countries, we find that delay in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…Currently, Mosaic provides data for 91 regions of historic Europe containing over 700,000 individuals living in 143,000 domestic groups from the Atlantic to the Urals (Szołtysek and Gruber 2014). Sources for NW and S Europe: Stolz et al (2012), see also Tollnek and Baten (2011); Southsouthern Europe in 1630 (1680) refers to the average value of Spain and Portugal during the period 1600-49 (1650-99), see Juif and Baten (2001).…”
Section: Results and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Mosaic provides data for 91 regions of historic Europe containing over 700,000 individuals living in 143,000 domestic groups from the Atlantic to the Urals (Szołtysek and Gruber 2014). Sources for NW and S Europe: Stolz et al (2012), see also Tollnek and Baten (2011); Southsouthern Europe in 1630 (1680) refers to the average value of Spain and Portugal during the period 1600-49 (1650-99), see Juif and Baten (2001).…”
Section: Results and Conclusionmentioning
confidence: 99%
“…What broad trends could be identified using this procedure, and how do they compare with those of other European regions? In Figure 7, data from eastern Europe were plotted against the evidence from western and southern European countries, which we derived from Stolz et al 2012 (see also Tollnek and Baten 2011). The authors assessed the northwestern and central European region (Austria, Germany, France, Sweden, and the UK), for which relatively continuous evidence from the 1730s is available, and the southern European region (Italy, Spain, Portugal).…”
Section: Eastern Europe In International Comparisonmentioning
confidence: 99%
“…Sample selection problems of the selection-on-unobervables type tend to be minimized when they are discussed at all. A recent study of Portuguese heights is typical in this regard (Stolz, Baten, and Reis 2013). Other researchers make a virtue of the oversampling of the poor and working classes, but this argument confuses the selection-on-observables type with the selection-on-unobservables type.…”
mentioning
confidence: 99%
“…We may thus conclude that our findings are not an underestimate of gross agricultural output. Per capita food intake offers us a second opportunity to corroborate our initial output findings, this time using evidence from the field of anthropometric history.52 A recent study regarding the evolution of the height of Portuguese males between 1720 and 1980 has shown that the standard of living and the level of human capital of this population were, in the long run, the principal determinants of stature (Stolz et al 2013). The first of these was measured by these authors using the real wage level, but in the present instance we employ average real food consumption instead.…”
Section: Are the Results Consistent?mentioning
confidence: 82%